Features of the formation, accounting and distribution of profits of an innovative enterprise - G.V. Berlyak; S.E. Pyrizhok (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Making a profit is a desirable financial result that all business entities strive for. To minimize the negative consequences of risk in innovative enterprises, it is necessary to create reserves. The article establishes that the directions for using the net profit of an innovative enterprise are determined at the legislative level, however, according to the specifics of innovation, it is recommended to include reserve (insurance) capital, a fund for the development and improvement of production, as well as other special purpose funds in fixed assets created from profit. These recommendations for the funds analyzed and proposed in the article are analytical sections for the needs of accounting support in accordance with the characteristics of the activities of newly created innovative enterprises. These reserves take into account the peculiarities of newly created innovative enterprises that ensure the development of the activities of such business entities, both at the initial stages of the development of activities, and for the purpose of further existence, and can also be used in the event of unfavorable business conditions to minimize the risks of activities and other negative phenomena.